2015
DOI: 10.11604/pamj.2015.20.143.5252
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices of contraception by HIV positive women followed in a Cameroon region with high illiteracy rate: a cross sectional study

Abstract: IntroductionTo evaluate the knowledge, attitude and practices of contraception by HIV positive women.MethodsThis cross-sectional descriptive study was carried out in the Maroua Regional Hospital (Cameroon) from September 1st, 2012 to February 28th, 2013. All HIV positive women aged between 15 and 49 years who were received in the HIV clinic were recruited. The variables recorded included maternal age, number of living children, marital status, religion, the educational level, and the use of antiretroviral trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 12 publications
5
10
0
1
Order By: Relevance
“…Having many children by WLHIV may be related to knowledge about pregnancy risks HIV-positive women are exposed to during pregnancy. Prior related studies have reported similar results in Ethiopia,24 Ghana,21 and Brazil 25. Hence, there may be need to include importance of having very few children in counselling WLHIV.…”
Section: Discussionsupporting
confidence: 51%
“…Having many children by WLHIV may be related to knowledge about pregnancy risks HIV-positive women are exposed to during pregnancy. Prior related studies have reported similar results in Ethiopia,24 Ghana,21 and Brazil 25. Hence, there may be need to include importance of having very few children in counselling WLHIV.…”
Section: Discussionsupporting
confidence: 51%
“…This finding suggests that respondents with higher education are more likely to go for family planning services than those with lower education. This agrees with several other studies that revealed that women with higher education status tends to be better informed about family planning services and have greater access to family planning and are more likely to use the service than their peers with lower education (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(26)(27)(28). This may be due to the influence education make on their decision making process.…”
Section: Discussionsupporting
confidence: 91%
“…The majority of the respondents were educated which is similar to a study done in Ghana (13). It was also found that two thirds of the respondents were Christians which is similar to a study done in Ghana (13) and contrasted to the study in Northern Nigerian where majority of the participants were Muslims (14) and that done in Cameroon (15) while over half of the respondents 57.4% were of the Yoruba speaking extraction which may be due to the fact that the study was carried out in the Yoruba speaking locality.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations